Horizontal alveolar ridge expansion followed by immediate placement of implants and rehabilitation with zirconia prosthesis - Tatiana Miranda Deliberador; Thalyta Verbicaro; Leonel Minerva; Rafaela Scariot; Allan Fernando Giovanini; João Césa Zielak (Wolters Kluwer Medknow Publications, 2017)
In recent years, there have been a growing number of procedures involving dental implants. Most cases, though, are characterized by bone atrophy, especially horizontal atrophy. This clinical case aims to report a technique for the expansion of the horizontal alveolar ridge. A longitudinal fracture was created in the alveolar ridge to expand the bone, followed by immediate insertion of dental implants along with a particulate allogeneic bone graft. Eight implants were placed in the maxilla, and after 12 months, a surgical reopening was performed, along with rehabilitation with a protocol-type prosthesis, for which a zirconia infrastructure was made. The patient was observed during a 10-month follow-up period in which an effective osseointegration of all implants was achieved as a result of such a technique. The split-crest technique followed by the immediate placement of implants and a particulate allogeneic bone graft proved to be effective, with a predictable osseointegration.